ANALISIS PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DAN NILAI PASAR PERUSAHAAN (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2012) - Feri Rachman; Marsono Marsono (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the influence of intellectual capital on the financial performance and market value of the company. This study also aims to analyze the influence between the components of intellectual capital, i.e.: human capital, customer capital, innovation capital, and process capital. Because of that the components of intellectual capital that became the core of forming a competitive advantage for the company were known.This study uses purposive sampling method which the determining of sample is based on certain criteria. The sample of this study is a secondary data which obtained from the financial statements of companies on the Indonesian Stock Exchange in 2008-2012. From all of those companies in 5 years period, 11 qualified companies were selected, so the total sample was 55. Data analysis was performed using analysis tools Partial Least Square (PLS).The result of this study shows that not all of intellectual capital components have significant effect to financial performance and market value of the company. Innovation capital has no effect to human capital, but it has significant effect to customer capital. Process capital has significant effect to customer capital. Human capital has no effect to customer capital, but it has significant effect to financial performance and market value of the company. Customer capital has no effect to financial performance and market value of the company. Financial performance has significant effect to market value of the company.